2014
DOI: 10.1111/jvs.12203
|View full text |Cite
|
Sign up to set email alerts
|

Distance to seed sources and land‐use history affect forest development over a long‐term heathland to forest succession

Abstract: Questions: Is there a spatial pattern in the community structure (stem densities, species richness and species composition) of trees and shrubs during more than 100yr of heathland to forest succession? To what extent is community structure influenced by land-use history and distance to seed sources? Do these effects change in time? Location: A 350-ha heathland (NOrholm) in southwest Denmark was abandoned in 1895 and left for free succession. Prior to abandonment the heathland was under traditional management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…The same effect was found in a successional study of this area, demonstrating that species richness and composition of trees were not in equilibrium with soil conditions (Kepfer‐Rojas et al. ). We cannot rule out, however, that this could be an effect mediated by the grass cover.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The same effect was found in a successional study of this area, demonstrating that species richness and composition of trees were not in equilibrium with soil conditions (Kepfer‐Rojas et al. ). We cannot rule out, however, that this could be an effect mediated by the grass cover.…”
Section: Discussionsupporting
confidence: 77%
“…However, previous work on this heathland attributed this negative effect to suppression of tree colonization by increased grass cover (particularly Deschampsia flexuosa ), mediated by nutrient availability (Kepfer‐Rojas et al. , ), which highlights the importance of the abiotic environment in regulating biotic interactions.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Distance to lava flow edge is considered as a proxy parameter for the proximity to seed sources, which is important for the start of vegetation recovery (Kepfer‐Rojas et al ., ). In general, NDVI is lower at longer distances from the lava flow edge (Figures and ); this could be explained by the fact that it is more difficult for seeds to reach bare lava surfaces – the number of seeds in a location decreases with the distance from the source (Howe and Smallwood, ; McClanahan, ; Nathan and Muller‐Landau, ).…”
Section: Discussionmentioning
confidence: 99%
“…If a population of some species establishes in a restored site, then it can become a part of a metapopulation with possible continuous interactions with the surroundings (Hanski ). In the case of vascular plants in some terrestrial habitats, it was shown that proximity (up to 100 m) to populations of target plant species dictated the degree to which restoration occurred spontaneously (del Moral et al ; Řehounková & Prach ), but some species may arrive from much longer distances (Kirmer et al ; Kepfer‐Rojas et al ).…”
Section: Introductionmentioning
confidence: 99%